2023
DOI: 10.1371/journal.pgen.1010831
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of factors that underlie transcriptional silencing in C. elegans oocytes

Abstract: While it has been appreciated for decades that prophase-arrested oocytes are transcriptionally silenced on a global level, the molecular pathways that promote silencing have remained elusive. Previous work in C. elegans has shown that both topoisomerase II (TOP-2) and condensin II collaborate with the H3K9me heterochromatin pathway to silence gene expression in the germline during L1 starvation, and that the PIE-1 protein silences the genome in the P-lineage of early embryos. Here, we show that all three of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Next, we used RNAi to deplete TOP-2. Our previous work, with these same RNAi conditions, has shown that loss of TOP-2 promotes unscheduled transcription in oocytes, spermatocytes, and starved Z2/Z3 (2,3,8). However, in one-or two-cell embryos, TOP-2 depletion had no impact on transcriptional repression (Fig 2C).…”
Section: One-and Two-cell Embryos Do Not Require Either Set-25 or Top...mentioning
confidence: 54%
See 4 more Smart Citations
“…Next, we used RNAi to deplete TOP-2. Our previous work, with these same RNAi conditions, has shown that loss of TOP-2 promotes unscheduled transcription in oocytes, spermatocytes, and starved Z2/Z3 (2,3,8). However, in one-or two-cell embryos, TOP-2 depletion had no impact on transcriptional repression (Fig 2C).…”
Section: One-and Two-cell Embryos Do Not Require Either Set-25 or Top...mentioning
confidence: 54%
“…One possibility is that TOP-2 requires the presence of PIE-1 to silence the genome. We have previously shown that this is true in oocytes, where loss of either PIE-1 or TOP-2 prevents transcriptional repression (2). By contrast, PIE-1 is not expressed in the Z2/Z3 PGCs and TOP-2 is nonetheless required for genome silencing during L1 starvation (8).…”
Section: Pie-1 Can Repress Transcription Outside Of the P-lineage Whe...mentioning
confidence: 96%
See 3 more Smart Citations